Polyamide composition as well as preparation method and application thereof
By introducing semi-aromatic polyamide resin and zirconium hydroxide into polyamide materials, the problem of electrochemical corrosion in high temperature and high humidity environments is solved, and the material's electrochemical corrosion resistance, mechanical properties and flame retardant properties are improved. It is suitable for high-voltage connectors and energy storage connectors and other fields.
Patent Information
- Application Number
- CN202411989400.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing organic phosphine halogen-free flame-retardant polyamide materials are prone to electrochemical corrosion in high temperature and high humidity environments, resulting in a drop in the insulation voltage of the material and is very easy to be broken down and failed.
A polyamide composition is prepared by introducing semiaromatic polyamide resin and zirconium hydroxide and limiting the amount of each component to a specific range. The π-π structure of semi-aromatic polyamide resin can interact with cations to reduce the number of free ions, while zirconium hydroxide is stable and selective, can coat phosphate ions and reduce electrochemical corrosion.
The polyamide composition significantly improves the electrochemical corrosion resistance under high temperature and high humidity conditions, and has excellent mechanical properties and flame retardant properties. It is suitable for new energy high-voltage connectors and energy storage connectors and other fields.
Smart Images

Figure CN119798983A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and in particular to a polyamide composition and a preparation method and application thereof. Background Art
[0002] Organophosphine halogen-free flame-retardant polyamide is widely used in high-voltage connectors, energy storage connectors, etc. due to its excellent comprehensive mechanical properties, easy coloring, easy processing, high CTI and other advantages. However, as the application environment of connectors (such as high temperature, high humidity, etc.) becomes more and more complex, the performance requirements for materials are also constantly upgrading, especially for high-voltage connectors, energy storage connectors and other components involving high voltage, the electrochemical corrosion performance of materials in high temperature and high humidity environments is increasingly concerned. Electrochemical corrosion will cause the surface resistance of the material to decrease, the insulation withstand voltage to drop, and it is very easy to be broken down and fail under high voltage or high current. Therefore, it is necessary to develop an organophosphine halogen-free flame-retardant polyamide material that not only has excellent electrochemical corrosion resistance under high temperature and high humidity conditions, but also has excellent mechanical properties and flame retardant properties. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present application is to provide a polyamide composition and a preparation method and application thereof, so as to improve the electrochemical corrosion resistance of the polyamide composition, especially the electrochemical corrosion resistance under high temperature and high humidity (such as temperature 85°C, humidity 85% RH) conditions, and make it have excellent mechanical properties and flame retardant properties.
[0004] In order to achieve the above objectives, in a first aspect, the present application provides a polyamide composition comprising the following components in parts by weight:
[0005]
[0006] Wherein, the polyamide resin comprises a semi-aromatic polyamide resin;
[0007] In the polyamide resin, the weight percentage of the semi-aromatic polyamide resin is ≥14%.
[0008] The organic phosphine flame retardants and flame retardant synergists used in organic phosphine halogen-free flame-retardant polyamide materials are usually highly acidic, which will promote the hydrolysis of polyamide, and they are easy to decompose during high-temperature processing. The small molecular substances produced by the decomposition are easy to precipitate on the surface of the material under high temperature and high humidity conditions. At the same time, the ions in the material are easy to form a primary battery reaction. The above factors will accelerate the electrochemical corrosion of the material. The inventors found during the research that the benzene ring of the semi-aromatic polyamide resin not only has barrier properties, but also its π-π structure can interact with cations, thereby reducing the number of free ions in the system; compared with other alkaline substances, such as oxides such as magnesium oxide, aluminum oxide, zinc oxide, zirconium oxide, and hydroxides such as magnesium hydroxide, aluminum hydroxide, zinc hydroxide, and boehmite, zirconium hydroxide can significantly improve the electrochemical corrosion performance of the material, which may be because zirconium hydroxide has good stability and compatibility with the matrix resin, and has strong selectivity for phosphate ions, and can also coat phosphate ions to greatly reduce electrochemical corrosion; by introducing semi-aromatic polyamide resin and zirconium hydroxide, and limiting the amount of the above components within a specific range, the obtained polyamide composition can have excellent mechanical properties (such as simply supported beam notched impact strength), flame retardant properties and electrochemical corrosion resistance, especially electrochemical corrosion resistance under high temperature and high humidity (such as temperature 85°C, humidity 85%RH) conditions.
[0009] In the polyamide resin, the weight percentage of the semi-aromatic polyamide resin is ≥14%, such as 14%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 100% or an interval formed by any two of the above values.
[0010] Preferably, the weight ratio of the semi-aromatic polyamide resin to the zirconium hydroxide is (35-130): 1. More preferably, the weight ratio of the semi-aromatic polyamide resin to the zirconium hydroxide is (48-102):1.
[0011] When the weight ratio of the semi-aromatic polyamide resin to the zirconium hydroxide is in the range of (35-130):1, especially in the range of (48-102):1, the electrochemical corrosion performance of the obtained composition is better. The weight ratio of the semi-aromatic polyamide resin to the zirconium hydroxide can be selected as 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1, 105:1, 110:1, 115:1, 120:1, 125:1, 130:1 or the interval formed by any two of the above values.
[0012] Preferably, the average particle size of the zirconium hydroxide is 0.5-4 μm. For example, the average particle size of the zirconium hydroxide is 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 4 μm or an interval formed by any two of the above values.
[0013] When the average particle size of the zirconium hydroxide is within the range of 0.5-4 μm, the obtained polyamide composition has good mechanical properties, such as higher simply supported beam notched impact strength.
[0014] The average particle size (Dv50) of the zirconium hydroxide can be measured using a laser particle size tester according to GB / T 19077-2016.
[0015] Preferably, the relative viscosity of the concentrated sulfuric acid solution of aromatic polyamide at 25° C. is 2.0 to 2.7, wherein the concentration of aromatic polyamide in the concentrated sulfuric acid solution of aromatic polyamide is 0.01 g / mL, H 2 SO 4 The concentration is 96wt.%.
[0016] When the relative viscosity of the concentrated sulfuric acid solution of the aromatic polyamide at 25° C. is in the range of 2.0 to 2.7, such as 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7 or an interval formed by any two of the above values, it is more conducive to the balance of material mechanical properties (such as simply supported beam notched impact strength, etc.) and processing performance.
[0017] Preferably, the semi-aromatic polyamide resin includes at least one of PA6T, PA9T, PA10T, PA12T, and nylon MXD6. More preferably, the semi-aromatic polyamide resin includes nylon MXD6. Nylon MXD6 has a lower melting point and better processing performance.
[0018] Preferably, the polyamide resin further comprises an aliphatic polyamide resin, and the weight of the semi-aromatic polyamide resin / the weight of the aliphatic polyamide resin is ≥ 1 / 6. More preferably, the weight of the semi-aromatic polyamide resin / the weight of the aliphatic polyamide resin is 1 / 6 to 7 / 1.
[0019] Compared with semi-aromatic polyamide resin, aliphatic polyamide resin is cheaper. When the weight of semi-aromatic polyamide resin / weight of aliphatic polyamide resin is controlled to be ≥ 1 / 6, especially in the range of 1 / 6 to 7 / 1, the obtained polyamide composition has a higher cost performance. The weight of semi-aromatic polyamide resin / weight of aliphatic polyamide resin can be selected as 1 / 6, 1 / 5, 1 / 4, 1 / 3, 1 / 2, 1 / 1, 2 / 1, 3 / 1, 4 / 1, 5 / 1, 6 / 1, 7 / 1, 8 / 1, 9 / 1, 10 / 1, 20 / 1, 40 / 1, 60 / 1, 80 / 1, 100 / 1, 500 / 1, 1000 / 1 or the interval formed by any two of the above values.
[0020] Preferably, the relative viscosity of the concentrated sulfuric acid solution of the aliphatic polyamide resin at 25° C. is 1.9 to 2.5, wherein the concentration of the aliphatic polyamide in the concentrated sulfuric acid solution of the aliphatic polyamide is 0.01 g / mL, H 2 SO 4 The concentration is 96wt.%.
[0021] When the relative viscosity of the concentrated sulfuric acid solution of the aliphatic polyamide resin at 25° C. is in the range of 1.9 to 2.5, such as 2.0, 2.1, 22, 2.3, 2.4, 2.5 or an interval formed by any two of the above values, it is more conducive to the balance of material mechanical properties (such as simply supported beam notched impact strength, etc.) and processing performance.
[0022] The relative viscosity of the concentrated sulfuric acid solution of the semi-aromatic polyamide resin at 25°C and the relative viscosity of the concentrated sulfuric acid solution of the aliphatic polyamide resin at 25°C can be measured according to the following method: 0.5g of polyamide resin is added to a 50mL volumetric flask, about 40mL of 96wt.% concentrated sulfuric acid is added, ultrasonic oscillation is performed until the polyamide resin is completely dissolved, the solution is cooled to 25°C, diluted to the scale with 96wt.% concentrated sulfuric acid, mixed and dispersed to obtain a polyamide resin solution with a concentration of 0.01g / mL, and the flow time of the solution through the Ubbelohde viscometer at 25°C is tested, which is recorded as t1; the flow time of the solvent 96wt.% concentrated sulfuric acid is tested using the same viscometer, which is recorded as t2, and t1 / t2 is the relative viscosity of the polyamide resin.
[0023] Preferably, the aliphatic polyamide resin comprises at least one of the condensation products of one or more dicarboxylic acids and one or more diamines, the condensation products of two or more aminocarboxylic acids, and the ring-opening polymerization products of one or more cyclic lactams. More preferably, the aliphatic polyamide resin comprises polyhexamethylene adipamide (ie, PA66).
[0024] Preferably, the organic phosphine flame retardant includes aluminum diethylphosphinate. Compared with other organic phosphine flame retardants, aluminum diethylphosphinate has a higher cost performance.
[0025] Preferably, the flame retardant synergist comprises at least one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate. More preferably, the flame retardant synergist comprises melamine polyphosphate to lower the cost.
[0026] Preferably, the glass fiber includes at least one of A glass fiber (high alkali glass fiber), C glass fiber (medium alkali glass fiber), D glass fiber, E glass fiber (alkali-free glass fiber), S glass fiber (special glass fiber), and quartz glass fiber.
[0027] Preferably, the glass fiber has an average diameter of 10-13 μm and an average aspect ratio of 280-330.
[0028] Without damaging the technical effect of the present application, the polyamide composition may further include at least one of an antioxidant and a lubricant, such as at least one of antioxidant 1098, montan ester, and the like.
[0029] Preferably, the weight percentage of the polyamide resin (ie, all polyamide resins) in the polyamide composition is above 30%, such as 30%, 40%, 50%, 60%, 70%, 79% or an interval formed by any two of the above values.
[0030] In a second aspect, the present application provides a method for preparing the polyamide composition, comprising the following steps:
[0031] All raw materials are mixed and dispersed, melt-extruded, and granulated to obtain a polyamide composition.
[0032] Preferably, the melt extrusion is carried out in a twin-screw extruder, the aspect ratio of the twin-screw extruder is 36:1-48:1, the screw speed is 300-800 rpm, the temperature of each section of the screw barrel is independently 160°C-330°C, and the head temperature is 280°C-330°C.
[0033] In a third aspect, the present application provides an application of the polyamide composition in a high voltage connector or an energy storage connector. In some embodiments, the operating voltage of the high voltage connector is 800V.
[0034] Compared with the prior art, the beneficial effect of the present application is that the polyamide composition of the present application utilizes an organic phosphine flame retardant and a flame retardant synergist to form a flame retardant system, and introduces aromatic polyamide and zirconium hydroxide to improve the electrochemical corrosion resistance. Under the synergistic effect of each component, the composition has excellent mechanical properties (such as simply supported beam notched impact strength), flame retardant properties and electrochemical corrosion resistance, especially electrochemical corrosion resistance under high temperature and high humidity conditions (such as temperature 85°C, humidity 85% RH), and has very good application prospects in the fields of new energy high-voltage connectors, energy storage connectors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a reference diagram for the electrochemical corrosion resistance evaluation standard (from left to right: no corrosion, slight corrosion, corrosion, severe corrosion). DETAILED DESCRIPTION
[0036] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0037] Each of the following examples and comparative examples provides a polyamide composition. The formulations of these polyamide compositions are shown in Table 1 and Table 2. Their preparation methods include the following steps: mixing and dispersing all raw materials and feeding them into a twin-screw extruder for granulation to obtain a polyamide composition, wherein the length-to-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 400 rpm, the temperature of each section of the screw barrel is independently 160° C. to 330° C., and the head temperature is 290° C. to 320° C.;
[0038] The raw material information used in the above examples and comparative examples is as follows, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind:
[0039] Semi-aromatic polyamide resin 1: nylon MXD6, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.2, model PA MXD6 M30L, manufacturer Beijing Anage Energy Engineering Technology Co., Ltd.;
[0040] Semi-aromatic polyamide resin 2: PA6T, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.2, model KFHP41, manufacturer Zhuhai Wantong Special Engineering Plastics Co., Ltd.;
[0041] Semi-aromatic polyamide resin 3: PA9T, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.2, model N1000A-M41, manufacturer Kuraray Trading (Shanghai) Co., Ltd.;
[0042] Semi-aromatic polyamide resin 4: PA10T, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.1, model KFHP611, manufacturer Zhuhai Wantong Special Engineering Plastics Co., Ltd.;
[0043] Semi-aromatic polyamide resin 5: PA12T, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.1, model PA12T 20N 00, manufacturer: Henan Junheng Industrial Group Biotechnology Co., Ltd.;
[0044] Aliphatic polyamide resin 1: PA66, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.0, model PA66U2501, manufacturer INVISTA Nylon Chemical (China) Co., Ltd.;
[0045] Aliphatic polyamide resin 2: PA56, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.2, model PA56E-2260, manufacturer Kaisai (Wusu) Biomaterials Co., Ltd.;
[0046] Aliphatic polyamide resin 3: PA610, the relative viscosity of its concentrated sulfuric acid solution at 25°C is 2.0, model PA610F120, manufacturer Shandong Guangyin New Materials Co., Ltd.;
[0047] Aluminum diethylphosphinate: Model Exolit OP 1230, manufacturer Clariant International AG;
[0048] Flame retardant synergist 1: melamine polyphosphate, model Budit 3141, manufacturer BUDENHEIMIBERICA, SLU;
[0049] Flame retardant synergist 2: melamine zinc polyphosphate, model Safire 400, manufacturer HUBERADVANCEDMATERIALS;
[0050] Flame retardant synergist 3: zinc borate, model ZB-503, manufacturer Anhui Yishitong Materials Technology Co., Ltd.;
[0051] Glass fiber: E glass fiber, average diameter 10 μm, average aspect ratio 300, model ECS10-03-568H, manufacturer China Jushi Co., Ltd.
[0052] Zirconium hydroxide 1: average particle size 1.0 μm, homemade;
[0053] Zirconium hydroxide 2: average particle size 2.2 μm, homemade;
[0054] Zirconium hydroxide 3: average particle size 3.0 μm, homemade;
[0055] Magnesium oxide: average particle size 1.5 μm, manufacturer Shandong Ocean Star Chemical Technology Co., Ltd.;
[0056] Zirconia: average particle size 1.6 μm, homemade;
[0057] Magnesium hydroxide: average particle size 1 μm, model Aitemag 12FD, manufacturer Jiangsu Aitek Flame Retardant Materials Co., Ltd.;
[0058] Boehmite: average particle size 1.5μm, model BG-613SO, manufacturer Anhui Yishitong Materials Technology Co., Ltd.
[0059] The test method for the relative viscosity of the concentrated sulfuric acid solutions of the above-mentioned semi-aromatic polyamide resins and aliphatic polyamide resins at 25°C is as follows: 0.5g of polyamide resin is added to a 50mL volumetric flask, and about 40mL of 96wt.% concentrated sulfuric acid is added, and ultrasonic oscillation is performed until the polyamide resin is completely dissolved, and the solution is cooled to 25°C, and diluted to the scale with 96wt.% concentrated sulfuric acid, and mixed and dispersed to obtain a polyamide resin solution with a concentration of 0.01g / mL, and the flow time of the solution through the Ubbelohde viscometer at 25°C is tested, and recorded as t1; the flow time of the solvent 96wt.% concentrated sulfuric acid is tested using the same viscometer, and recorded as t2, and t1 / t2 is the relative viscosity of the polyamide resin.
[0060] The above-mentioned zirconium oxide preparation method is as follows: provide zirconium oxide coarse powder (average particle size 7 μm), purchased from Xi'an Fangke New Material Technology Co., Ltd.; grind it with a planetary ball mill and sieve it with an 8000 mesh sieve to obtain zirconium oxide fine powder with an average particle size of 1.6 μm.
[0061] The above-mentioned zirconium hydroxide preparation method is as follows: provide zirconium hydroxide (model: TZH-85H; average particle size 25μm), which is purchased from Qingdao Tianyao Industrial Co., Ltd.; after grinding with a planetary ball mill, sieve with 11000 mesh, 6000 mesh and 4000 mesh sieves respectively to obtain zirconium hydroxide fine powder with average particle sizes of 1.0μm, 2.2μm and 3.0μm.
[0062] The following performance tests were performed on the polyamide compositions of the above embodiments and comparative examples:
[0063] 1) Surface precipitation: Place a 100*100*3mm sample in an environmental box at 85°C and 85%RH for 500 hours, and visually evaluate the state of the surface precipitation. According to the degree of precipitation, it is divided into no precipitation, slight precipitation (point precipitation), precipitation (line precipitation), and severe precipitation (surface precipitation);
[0064] 2) Electrochemical corrosion resistance: A cylindrical copper wire with a diameter of 1 cm was inserted into the polyamide composition, the voltage was 1 kV, and the device was placed in an environmental box at 85°C and 85% RH for 500 h. At the end of the experiment, the electrochemical corrosion performance was evaluated by evaluating the corrosion degree of the copper wire surface in contact with the polyamide composition, referring to Figure 1 , according to the degree of corrosion, it is divided into four levels from light to heavy: no corrosion, slight corrosion, corrosion, and severe corrosion;
[0065] 3) The flame retardant grade test is carried out in accordance with UL 94 standard, and the test specimen size is 125mm*13mm*1.6mm;
[0066] 4) Simply supported beam notched impact performance: According to ISO 179-1:2010 method, the test specimen size is 80*10*4mm, A-type notch.
[0067] The test results are shown in Table 3.
[0068] Table 1
[0069]
[0070] Table 2
[0071]
[0072]
[0073] Table 3
[0074]
[0075] It can be seen from the above data that the compositions of each embodiment have excellent mechanical properties (such as simple supported beam notched impact strength), flame retardancy, moisture and heat resistance and electrochemical corrosion resistance, especially electrochemical corrosion resistance under high temperature and high humidity (such as temperature 85°C, humidity 85% RH) conditions, among which the simple supported beam notched impact strength is 10J / m 2 The flame retardant grade is above V-0. There is no or slight precipitation on the surface after 500 hours at 85°C and 85%RH. There is no or slight corrosion on the surface after 500 hours of electrochemical corrosion at 85°C, 85%RH and 1kV.
[0076] Comparison of Examples 1, 8 to 11 with Comparative Example 1 shows that, compared with aliphatic polyamide resin, the use of semi-aromatic polyamide resin is beneficial to improving the electrochemical corrosion performance of the material.
[0077] Comparison between Examples 1, 15-16 and Comparative Examples 2, 4-7 shows that the addition of zirconium hydroxide as an electrochemical stabilizer can significantly improve the electrochemical corrosion resistance of the material, and keep the material with high mechanical properties and good flame retardancy; the addition of oxides such as magnesium oxide and zirconium oxide does not significantly improve the electrochemical corrosion resistance of the material, because these oxides have poor compatibility with the matrix resin, and zirconium oxide has a large hardness, which will grind the glass fiber, thus having a greater impact on the mechanical properties of the material; the addition of hydroxides such as magnesium hydroxide is easy to decompose and has little effect on improving the electrochemical corrosion performance; the addition of boehmite, because boehmite mainly uses porous structure to absorb acid, has a weak effect on improving electrochemical corrosion. Comparison between Examples 1-7 and Comparative Example 3 shows that the addition amount of zirconium hydroxide should not be too much, otherwise it will weaken the toughness of the product.
[0078] By comparing Examples 1 and 4 to 7, it can be seen that when the total amount of aromatic polyamide and zirconium hydroxide added is constant and the weight ratio of the two is in the range of (48 to 102):1, the comprehensive mechanical, moisture and heat resistance and electrochemical corrosion resistance properties of the product are better.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A polyamide composition, characterized in that It comprises the following components in parts by weight: Wherein, the polyamide resin comprises a semi-aromatic polyamide resin; In the polyamide resin, the weight percentage of the semi-aromatic polyamide resin is ≥14%.
2. The polyamide composition according to claim 1, characterized in that The weight ratio of the semi-aromatic polyamide resin to the zirconium hydroxide is (35-200):1, preferably (48-102):
1.
3. The polyamide composition according to claim 1, characterized in that The average particle size of the zirconium hydroxide is 0.5-4 μm.
4. The polyamide composition according to claim 1, characterized in that The semi-aromatic polyamide resin satisfies at least one of the following conditions: S1. The relative viscosity of the concentrated sulfuric acid solution of the aromatic polyamide at 25°C is 2.0 to 2.7, wherein the concentration of the aromatic polyamide in the concentrated sulfuric acid solution of the aromatic polyamide is 0.01 g / mL, and the concentration of H2SO4 is 96wt.%; S2. The semi-aromatic polyamide resin includes at least one of PA6T, PA9T, PA10T, PA12T, and nylon MXD6.
5. The polyamide composition according to claim 1, characterized in that The polyamide resin further comprises an aliphatic polyamide resin, and the weight of the semi-aromatic polyamide resin / the weight of the aliphatic polyamide resin is ≥ 1 / 6, preferably 1 / 6 to 7 / 1.
6. The polyamide composition according to claim 5, characterized in that The aliphatic polyamide resin satisfies at least one of the following conditions: S3. The relative viscosity of the aliphatic polyamide resin is 1.9 to 2.5, and the test method is to measure the relative viscosity of the aliphatic polyamide at a concentration of 0.01 g / mL in concentrated sulfuric acid at 25°C, wherein the concentration of H2SO4 in the concentrated sulfuric acid is 96wt.%; S4. The aliphatic polyamide resin includes at least one of PA66, PA56, PA610, PA1212, and PA6.
7. The polyamide composition according to claim 1, characterized in that The organic phosphine flame retardant includes aluminum diethylphosphinate; the flame retardant synergist includes at least one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate.
8. The polyamide composition according to claim 1, characterized in that The glass fiber meets at least one of the following conditions: S5. The glass fiber includes at least one of A glass fiber, C glass fiber, D glass fiber, E glass fiber, S glass fiber, and quartz glass fiber; S6. The average diameter of the glass fiber is 10-13 μm, and the average aspect ratio is 280-330.
9. The method for preparing a polyamide composition according to any one of claims 1 to 8, characterized in that: All raw materials are mixed and dispersed, melt-extruded, and granulated to obtain a polyamide composition.
10. Use of the polyamide composition according to any one of claims 1 to 8 in a high voltage connector or an energy storage connector.
Citation Information
Patent Citations
Flame-retardant polyamide resin composition
CN113412298A
Low-mold-scale halogen-free flame-retardant reinforced nylon material and preparation method thereof
CN116355405A
Low-precipitation low-metal-corrosion flame-retardant polyamide composition as well as preparation method and application thereof
CN118344729A
Halogen-free flame-retardant semi-aromatic polyamide composite material, preparation method therefor, and use thereof
WO2024066970A1
Flame-retardant polyamide composite material, and preparation method therefor and use thereof
WO2024131454A1
Cited By
Polyamide composite material as well as preparation method and application thereof
CN121022094A
Polyamide composite material as well as preparation method and application thereof
CN121450096A